Experience with high-dose gadolinium MR imaging in the evaluation of brain metastases. - Yuh, W T; Engelken, J D; Muhonen, M G; Mayr, N A; Fisher, D J; Ehrhardt, J C (American Journal of Neuroradiology, 1992)
PURPOSE To assess the effectiveness and safety of higher doses of gadoteridol in the MR evaluation of patients with brain metastases.MATERIALS AND METHODS Thirty-one patients with a clinical suspicion of brain metastases were studied prospectively with gadoteridol, a new, nonionic, low-osmolality contrast agent. Each patient received an initial injection of 0.1 mmol/kg and an additional dose of 0.2 mmol/kg 30 minutes later. Images were obtained before, immediately after, and 10 and 20 minutes after the initial dose. Images also were acquired immediately after the additional dose of gadoteridol.RESULTS No adverse effects were attributed to the injection of gadoteridol. Four patients' examinations were excluded from analysis because of machine malfunction (two patients) and excessive motion artifact (two patients). Four patients had no detectable metastases. After the additional dose of gadoteridol, there was a marked qualitative improvement in lesion conspicuity and detection. The conspicuity of 80 of 81 lesions was increased in the high-dose studies, and 46 new lesions were detected in 19 of 27 patients. Quantitative image analysis demonstrated a significant increase in normalized mean lesion contrast between the initial-dose and high-dose studies (35 lesions identified in 13 patients, P less than .0001). The additional information gained by high-dose examinations contributed to a potential modification of the treatment in 10 of 27 patients. High-dose examinations increased flow-related artifact in the posterior fossa in 12 of 27 patients.CONCLUSION Based on our preliminary results, high-dose gadolinium-enhanced MR examinations may have advantages over 0.1 mmol/kg examinations in detecting early and/or small metastases. This may be significant in the management of patients with cerebral metastases.